(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Baptists in Romania, Victims of the Nationalist Discourse after the Great Unification of 1918 and Advocates of the Nationalist Discourse a Century Later This paper briefly explores the conditions of Romanian Baptist believers after the Great Unification of 1918. The main focus in the first part of the paper is on the persecution suffered by the Baptist community due to the actions undertaken by the State in Collaboration with the Orthodox Church in the ‘20s, based on a profound nationalist discourse. In the second part of the paper the author brings into discussion an unexpected shift regarding the nationalist discourse on behalf of the Baptist community in present day Romania. If one century ago baptist believers were victims of the nationalist discourse, now it seems that they are among the adherents – at least this seems to be the case for some of their leaders. In the section reserved for the conclusions the author tries to provide a pragmatic reasoning why this phenomenon occurred.